Pediatric Narcolepsy-A Practical Review - I-Hang Chung; Wei-Chih Chin; Yu-Shu Huang; Chih-Huan Wang (MDPI AG, 2022)
Pediatric narcolepsy is a chronic sleep-wakefulness disorder. Its symptoms frequently begin in childhood. This review article examined the literature for research reporting on the effects of treatment of pediatric narcolepsy, as well as proposed etiology and diagnostic tools. Symptoms of pediatric narcolepsy include excessive sleepiness and cataplexy. In addition, rapid-eye-movement-related phenomena such as sleep paralysis, sleep terror, and hypnagogic or hypnapompic hallucinations can also occur. These symptoms impaired children's function and negatively influenced their social interaction, studying, quality of life, and may further lead to emotional and behavioral problems. Therefore, early diagnosis and intervention are essential for children's development. Moreover, there are differences in clinical experiences between Asian and Western population. The treatment of pediatric narcolepsy should be comprehensive. In this article, we review pediatric narcolepsy and its treatment approach: medication, behavioral modification, and education/mental support. Pharmacological treatment including some promising newly-developed medication can decrease cataplexy and daytime sleepiness in children with narcolepsy. Other forms of management such as psychosocial interventions involve close cooperation between children, school, family, medical personnel, and can further assist their adjustment.